Molecular Imaging to Identify Tumor Recurrence following Chemoradiation in a Hostile Surgical Environment - Olugbenga T. Okusanya; Charuhas Deshpande; Eduardo M. Barbosa; Charu Aggarwal; Charles B. Simone; Jack Jiang; Ryan Judy; Elizabeth DeJesus; Steve Albelda; Shuming Nie; Philip S. Low; Sunil Singhal (Molecular Imaging)
Surgical biopsy of potential tumor recurrence is a common challenge facing oncologists, surgeons, and cancer patients. Imaging modalities have limited ability to accurately detect recurrent cancer in fields affected by previous surgery, chemotherapy, or radiation. However, definitive tissue diagnosis is often needed to initiate treatment and to direct therapy. We sought to determine if a targeted fluorescent intraoperative molecular imaging technique could be applied in a clinical setting to assist a surgical biopsy in a “hostile” field. We describe the use of a folate-fluorescein conjugate to direct the biopsy of a suspected recurrent lung adenocarcinoma invading the mediastinum that had been previously treated with chemoradiation. We found that intraoperative imaging allowed the identification of small viable tumor deposits that were otherwise indistinguishable from scar and necrosis. Our operative observations were confirmed by histology, fluorescence microscopy, and immunohistochemistry. Our results demonstrate one possible application and clinical value of intraoperative molecular imaging.